Physiology-Related Variations in the Blood Hormone and Metabolome of Endangered Hog Deer (Axis porcinus) - Juan Wen; Bo Zhao; Yuqin Cao; Yu Qu; Liming Chang; Jie Mao; Yufei Li; Ruoyao Ni; Runliang Zhai; Jianping Jiang; Wei Zhu; Xuanzhen Liu (Metabolites, 2025)
Background/Objectives: The hog deer (Axis porcinus) is an endangered species facing significant threats from habitat loss and fragmentation, with only captive populations remaining in China. Expanding breeding programs and restoring wild populations are critical strategies for the species’ conservation. Achieving this requires the development of an effective health database and the identification of molecular biomarkers for their physiological traits. Methods: In this study, we present the largest blood metabolomics dataset to date for captive hog deer, comprising 73 healthy individuals. We conducted targeted metabolomics to quantify blood hormone levels and untargeted metabolomics to characterize blood metabolic profiles, aiming to evaluate the associations of sex, age, and weight with metabolic profiles. Results: Our results reveal distinct growth patterns between females and males, with males reaching their body weight plateau at a larger size. We observed significant sex differences (p < 0.05) in blood hormones and metabolic profiles. Females exhibited higher levels of progesterone, hydroxyprogesterone, stress hormones (e.g., cortisol), and proline, while males had higher levels of testosterone, uric acid, phenylalanine, and guanidinosuccinic acid. Notably, body weight emerged as a more important factor than gender in explaining variations in the metabolome, particularly in males. Several blood biomarkers were identified as correlating with age and body weight. Specifically, blood progesterone levels in females were linked to both age and body weight, while in males, uric acid, prolylhydroxyproline, and 3-methylhistidine were associated with these factors. The potential significance of these results for the artificial breeding and conservation of hog deer were discussed. Conclusions: Our study provides a metabolic reference for identifying abnormal individuals and offers potential biomarkers for determining the gender, age, and body weight of hog deer. These findings may have significant implications for the artificial breeding and conservation efforts of the species.